Stack Inspection: Theory and Variants - Fournet, Cédric; Gordon, Andy (ACM Press, 2002)
Stack inspection is a security mechanism implemented in runtimes such as the JVM and the CLR to accommodate components with diverse levels of trust. Although stack inspection enables the fine-grained expression of access control policies, it has rather a complex and subtle semantics. We present a formal semantics and an equational theory to explain how stack inspection affects program behaviour and code optimisations. We discuss the security properties enforced by stack inspection, and also consider variants with stronger, simpler properties.
Proceedings of Tenth Conference on Uncertainty in Artificial Intelligence